2020
DOI: 10.1111/tpj.15082
|View full text |Cite
|
Sign up to set email alerts
|

Functional requirement of the Arabidopsis importin‐α nuclear transport receptor family in autoimmunity mediated by the NLR protein SNC1

Abstract: IMPORTIN-a3/MOS6 (MODIFIER OF SNC1, 6) is one of nine importin-a isoforms in Arabidopsis that recruit nuclear localization signal-containing cargo proteins to the nuclear import machinery. IMP-a3/MOS6 is required genetically for full autoimmunity of the nucleotide-binding leucine-rich repeat immune receptor mutant snc1 (suppressor of npr1-1, constitutive 1) and MOS6 also contributes to basal disease resistance. Here, we investigated the contribution of the other importin-a genes to both types of immune respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 84 publications
2
20
0
Order By: Relevance
“…Alternatively, a largely redundant repertoire of import adaptors could present a strategy to effectively buffer and protect vital signaling pathways. Indeed, the loss of a single importin -α gene has no obvious morphological consequences in Arabidopsis , while higher order mutants of IMP-α1 / 2 / 3 display a stunted growth morphology ( Chen et al, 2020 ; Lüdke et al, 2021 ). Chen et al (2020) also reported that triple mutant plants of IMP-α1 / 2 / 3 flower early and accordingly, the authors identified the three α-importins as adaptors that import LIKE HETEROCHROMATIN PROTEIN1 (LHP1; Table 1 ).…”
Section: Npc and Ntr Functions In Plant Development And Environmental Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, a largely redundant repertoire of import adaptors could present a strategy to effectively buffer and protect vital signaling pathways. Indeed, the loss of a single importin -α gene has no obvious morphological consequences in Arabidopsis , while higher order mutants of IMP-α1 / 2 / 3 display a stunted growth morphology ( Chen et al, 2020 ; Lüdke et al, 2021 ). Chen et al (2020) also reported that triple mutant plants of IMP-α1 / 2 / 3 flower early and accordingly, the authors identified the three α-importins as adaptors that import LIKE HETEROCHROMATIN PROTEIN1 (LHP1; Table 1 ).…”
Section: Npc and Ntr Functions In Plant Development And Environmental Responsesmentioning
confidence: 99%
“…Besides its partially redundant role with IMP-α1 and -α2 in plant development, a selective role of IMP-α3 has been described in immunity ( Lüdke et al, 2021 ). Based on the genetic requirement for the autoimmune phenotype of suppressor of npr1−1, constitutive1 ( snc1 ), a gain-of-function mutant of a nucleotide−binding leucine−rich repeat (NLR) immune receptor, IMP-α3 was named MODIFIER OF SNC1, 6 ( MOS6 ; Palma et al, 2005 ).…”
Section: Npc and Ntr Functions In Plant Development And Environmental Responsesmentioning
confidence: 99%
See 3 more Smart Citations